Characterizing the evolution of oculomotor and vestibulo-ocular function over time in children and adolescents after a mild traumatic brain injury - Crampton, Adrienne; Schneider, Kathryn J.; Grilli, Lisa; Chevignard, Mathilde; Katz-Leurer, Michal; Beauchamp, Miriam H.; Debert, Chantel; Gagnon, Isabelle J. (Frontiers in Neurology, 2022)
Background: Impairments to oculomotor (OM) and vestibulo-ocular reflex (VOR) function following pediatric mTBI have been demonstrated but are poorly understood. Such impairments can be associated with more negative prognosis, affecting physical and mental well-being, emphasizing the need to more fully understand how these evolve. Objectives: to determine i) the extent to which performance on clinical and computerized tests of OM and VOR function varies over time in children and adolescents at 21 days, 3-, and 6-months post-mTBI; ii) the proportion of children and adolescents with mTBI presenting with abnormal scores on these tests at each timepoint. Design: Prospective longitudinal design Setting: Tertiary care pediatric hospital. Participants: 36 participants with mTBI aged 6 to18. Procedures: Participants were assessed on a battery of OM and VOR tests within 21 days, at 3- and 6-months post injury. Outcome measures: Clinical measures: Vestibular/ocular motor screening tool (VOMS) (symptom provocation and performance); Computerized measures: reflexive saccade test (response latency), video head impulse test (VOR gain), and dynamic visual acuity test (LogMAR change). Analysis: Generalized estimating equations (parameter estimates and odd ratios) estimated the effect of time. Proportions above and below normal cut-off values were determined. Results: Our sample consisted of 52.8% females (mean age 13.98 (2.4) years, assessed on average 19.07 (8-33) days post-injury). An effect of age on visual motion sensitivity (OR 1.43, p=0.03) and sex on near point of convergence (OR 0.19, p=0.03) was identified. Change over time was demonstrated by VOMS overall symptom provocation (OR 9.90, p=0.012), vertical smooth pursuit (OR 4.04, p=0.03) and voluntary saccade performance (OR 6.06, p=0.005) and right VOR gain (0.068, p=0.013). Version performance and VOR symptom provocation showed high abnormal proportions at initial assessment. Discussion: Results indicate impairments to the VOR pathway may be present and may drive symptom provocation. Vertical smooth pursuit and saccade findings underline the need to include these tasks in test batteries to comprehensively assess the integrity of OM and vestibular systems post-mTBI. Implications: Findings demonstrate 1) added value in including symptom and performance-based measures in when OM and VOR assessments; 2) the relative stability of constructs measured beyond 3 months post mTBI.